Difference between Type 1 And 2 Diabetes Mellitus - Bereda, Gudisa (Jour Med Resh and Health Sci, 2022)
Type 1 diabetes mellitus involves autoimmune destruction of pancreatic beta cells which create insulin. The American Diabetes Association (ADA) defines type 1 diabetes mellitus (T1DM) as autoimmune ?-cell destruction, usually leading to absolute insulin deficiency. In type 1 diabetes mellitus the pancreatic beta cells primarily lost. Type 1 diabetes is characterized by a progressive loss of insulin producing beta cells in pancreatic islets. The immune destruction of beta cells is partly mediated by high levels of pro-inflammatory cytokines. Type 2 diabetes mellitus also named as non-insulin dependent diabetes mellitus and adult onset diabetes mellitus. The American Diabetes Association (ADA) defines type 2 diabetes mellitus (T2DM) as progressive loss of ?-cell insulin secretion frequently occurring on the background of insulin resistance. Type 2 diabetes is characterised by impaired beta cell function and insulin sensitivity and is often accompanied by other metabolic abnormalities.